The study of the mitigation strategy of Lungmen ABWR nuclear power plant using RELAP5 and FRAPTRAN with the interface SNAP. (February 2018) - Li, Wan-Yun; Wang, Jong-Rong; Huang, Wen-Shu; Chen, Shao-Wen; Shih, Chunkuan; Chiang, Show-Chyuan; Yu, Tzu-Yao
Highlights: The mitigation strategies study using RELAP5 and FRAPTRAN models was performed. Under Fukushima-like conditions, the analyses present that the strategies maintain the PCT below 1088.7 K. The controlled depressurization should be performed before the full depressurization. The RELAP5 predictions are consistent with TRACE. The FRAPTRAN results show that the fuel integrity for using strategies case is maintained. Abstract: In this study, the model of Lungmen ABWR NPP (nuclear power plant) using RELAP5 with the interface SNAP was established. This RELAP5/SNAP model performed the mitigation strategy simulation and study. The main systems of the mitigation strategy are RCIC (Reactor Core Isolation Cooling System), ADS (Automatic Depressurization System), and AC-Independent Water Addition System (ACIWA). This research focuses to assess the usefulness of the mitigation strategy under Fukushima-like conditions. There are three steps in this study. The first step is the establishment of Lungmen NPP RELAP5/SNAP model using the systems data, startup tests reports, and FSAR. The second step is the mitigation strategy simulation and analysis under Fukushima-like conditions using the RELAP5/SNAP model. In this step, the case without mitigation strategy was also performed to evaluate the mitigation strategy effectiveness. Finally, the FRAPTRAN analysis with the interface SNAP was performed in this study. This can evaluate the mechanical property and integrity of fuel rods. According to the RELAP5 results under Fukushima-like conditions, the mitigation strategy can maintain the PCT (peak cladding temperature) below the criteria (1088.7 K). And the FRAPTRAN results also present that the mitigation strategy can keep the fuel rods integrity. It indicates that Lungmen NPP would be in a safe situation when Lungmen NPP performs the mitigation strategy.